2023
DOI: 10.1186/s12871-023-02240-8
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia quality index improves the quality of postoperative pain management: a retrospective observational study of 14,747 patients between 2014 and 2021

Di Wang,
Yihui Guo,
Qian Yin
et al.

Abstract: Background The application of artificial intelligence patient-controlled analgesia (AI-PCA) facilitates the remote monitoring of analgesia management, the implementation of mobile ward rounds, and the automatic recording of all types of key data in the clinical setting. However, it cannot quantify the quality of postoperative analgesia management. This study aimed to establish an index (analgesia quality index (AQI)) to re-monitor and re-evaluate the system, equipment, medical staff and degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…While many valued participation in Ai-PCA training and were willing to address work-related issues collaboratively, attitudes towards updating knowledge and learning the latest expert consensus were less proactive. This nding aligns with reports from pain management guidelines indicating fewer advanced strategies employed in patient treatment in China [27]. Insu cient attention is directed towards the prevention and treatment of adverse events.…”
Section: Discussionsupporting
confidence: 78%
“…While many valued participation in Ai-PCA training and were willing to address work-related issues collaboratively, attitudes towards updating knowledge and learning the latest expert consensus were less proactive. This nding aligns with reports from pain management guidelines indicating fewer advanced strategies employed in patient treatment in China [27]. Insu cient attention is directed towards the prevention and treatment of adverse events.…”
Section: Discussionsupporting
confidence: 78%
“…The Questionnaire was developed with guidance from the “Intelligent Patient-Controlled Pain Management Expert Consensus”, 12 and relevant literatures. 3 , 13 , 14 The initial draft underwent revisions based on feedback from two senior experts specializing in anesthesia and thoracic surgery both holding the title of Chief Physician. Subsequently, a preliminary trial was conducted on a limited scale (n=48), resulting in a Cronbach’s alpha coefficient value of 0.875, indicating good internal consistency.…”
Section: Methodsmentioning
confidence: 99%
“…For example, wearable devices or mobile applications could track pain levels throughout the day, alert healthcare providers, and prevent pain-related complications [ 55 ]. A recent study compared postoperative analgesia by traditional management versus the application of the newly introduced “analgesia quality index” (AQI) through the application of AI-patient controlled analgesia (AI-PCA) and showed that the AQI decreased the incidence of moderate-to-severe pain, improved the quality of analgesia, and may provide guidance for optimum postoperative pain management [ 93 ]. However, the monitoring of physical activity may be affected by many factors, such as personal mood, weather conditions, and other psychosocial factors [ 94 , 95 ].…”
Section: Incorporation Of Artificial Intelligence For Objective Pain ...mentioning
confidence: 99%
“…The utilization of AI algorithms in pain assessment enables the analysis of large-scale datasets, pattern identification, and the emergence of trends and correlations within these datasets, leading to valuable insights into pain mechanisms, risk factors, and treatment efficacy. Clinical studies showed that the application of AI-based algorithms is associated with better pain relief and improved quality of analgesia [ 8 , 15 , 93 , 106 ]. Clinical application can provide guidance for optimum pain management in a postoperative setting [ 93 , 106 ].…”
Section: Incorporation Of Artificial Intelligence For Objective Pain ...mentioning
confidence: 99%
See 1 more Smart Citation